PENGARUH SUBJECTIVE WELL BEING DAN PSYCHOLOGY CAPITAL TERHADAP KINERJA PEGAWAI KANTOR BANK BJB CABANG MAKASSAR - Ifah finatry latiep; Godlive Purba; Hasbiyadi; Ardiansyah Halim; Firmansyah Halim (J-MSDM (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2024)
Determining the impact of Subjective Well-Being and Psychology Capital on Employee Performance at the BJB Bank Makassar Branch Office is the primary objective of this study. Quantitative research methods were used in this study. Within this investigation, 48 participants were selected as a sample. This study used SPSS-assisted multiple linear regression analysis on data collected from respondents and records kept at the BJB Bank Makassar Branch Office. This study found that employees' subjective well-being and psychological capital had a favourable and statistically significant impact on their performance at the Bank BJB Makassar Branch. Employee performance at Bank BJB's Makassar Branch is primarily affected by the psychological capital variable, out of the two significant independent factors.